Persepsi Etis Pelaku Akuntansi Terhadap Praktik Manajemen Laba Berdasarkan Profesi Akuntansi Dan Jender - Komala Inggarwati; Arnold Kaudin (Universitas Airlangga, 2010)
Managerial discretions in accounting and presures from stakeholders encourage earnings management. Such a practice creates ethical problems in business. The purpose of this study is to observe ethical perceptions in earnings management from acountants, both academics and profesional accountants, and ethical perceptions based on gender. Earnings management is classified into manipulation in accounting activity and in operational decision making. This study covers 156 subjects consists of 65 professional accountants from three public accountant firms and five companies and 91 academics from two universities in Central Java. Seven questions/cases adopted from Merchant (1989) and Fischer dan Rosenzweig (1995) were introduced to subjects and subjects were asked to assess whether it was ethical or not on a scale of 5 where 1 indicates the most ethical and 5 indicates the most unethical. The findings show that academics see manipulation in operational decision making as less ethical compared to practitioners while practitioners see manipulation in accounting as less ethical. Furthermore, practitioners see manipulation in operational decision as more ethical than manipulation in accounting while for academics there is no significant differences. Finally, there is not any significant difference on the ethical perception between female and male